Mediação familiar: diálogo interdisciplinar - Barros, Juliana Maria Polloni de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The historical construction of work with families has led to the interdisciplinary practice. There are many professionals that directly or indirectly, work with families and these various knowledge have interacted in order to expand and qualify the possibilities that may be useful to families. In this research we investigated the familiar mediation as a privileged locus to interdisciplinary work, seeking to bring contributions to those who work with families, through the field research, developed under the social constructionism’s perspective. Collection and data analysis were done under the theoretical-methodological proposal of the study of the production of meaning trough the analysis of discursive practices, chosen to promote a multiplicity of voices, perspectives and possibilities, consistent with the plural view of families and the mediation as one of possibilities in solving familiar conflicts. We worked up the idea of interdisciplinarity, aiming to think in the dialogue approach among the various areas of knowledge working with families. The meaning of word dialogue used here refers to the etymological sense of word: through the knowledge. Thus, we developed the research seeking the interdisciplinary dialogue as a conversation between different knowledge, collaboratively, seeking intersection’s points and agreements, respecting the diverse knowledge, with no hierarchy and, specially, in an ethical manner when working with the served families and the involved professionals. This work is addressed to all professionals who serve families and have the purpose to present mediation to the Social Service, with its potential and possibilities to families. It was found that the familiar mediation provides autonomy to the subjects in order to promote, through themselves, changes in their relationships, assisted by an ethically compromised professional: the mediator. Although the research shows that familiar mediation is a privileged...

A construção histórica do trabalho com as famílias tem levado à prática interdisciplinar. Muitas são as profissões que atuam direta ou indiretamente com as famílias e esses diversos saberes têm interagido de forma a ampliar e qualificar as possibilidades que possam ser úteis às famílias. Nesta pesquisa investigamos a mediação familiar como locus privilegiado para a atuação interdisciplinar, buscando trazer contribuições à prática profissional daqueles que atuam junto às famílias, por meio de pesquisa de campo, desenvolvida sob a perspectiva construcionista social. A obtenção e análise dos dados se deu sob a proposta teórico-metodológica do estudo da produção de sentidos por meio da análise das práticas discursivas, escolhida por favorecer a multiplicidade de vozes, olhares e possibilidades, em coerência com a visão plural de famílias e da mediação como uma das possibilidades de resolução de conflitos familiares. Trabalhamos com a ideia de interdisciplinaridade, no sentido de pensar no diálogo de aproximação entre as diversas áreas do saber que atuam com famílias. O sentido da palavra diálogo neste trabalho remete-se ao sentido etimológico da palavra: por meio do conhecimento. Assim, desenvolvemos a pesquisa buscando o diálogo interdisciplinar como uma conversa entre os saberes, de forma colaborativa, buscando pontos de interseção e entendimentos, com respeito pelo saber diferente, sem hierarquia e, especialmente, de forma ética em relação às famílias atendidas e aos profissionais envolvidos. Este trabalho se dirige à todos os profissionais que trabalham com famílias e tem como um de seus propósitos o de apresentar a mediação para o Serviço Social, com suas potencialidades e possibilidades junto às famílias. Constatamos que a mediação familiar favorece a autonomia dos sujeitos em promoverem por si as mudanças em suas relações, por meio da facilitação de um profissional eticamente...
Keywords: Serviço social - Prática; Mediação familiar; Assistentes sociais; Abordagem interdisciplinar do conhecimento; Serviço social com a familia; Mediação - Aspectos jurídicos - Brasil; Direito de familia; Social service